Referring physicians' intention to use hospital report cards for hospital referral purposes in the presence or absence of patient-reported outcomes: a randomized trial - Emmert, Martin; Schindler, Anja; Heppe, Laura; Sander, Uwe; Patzelt, Christiane; Lauerer, Michael; Nagel, Eckhard; Frömke, Cornelia; Schöffski, Oliver; Drach, Cordula (European Journal of Health Economics, 2023)
Purpose: This study aims to determine the intention to use hospital report cards (HRCs) for hospital referral purposes in the presence or absence of patient-reported outcomes (PROs) as well as to explore the relevance of publicly available hospital performance information from the perspective of referring physicians. Methods: We identified the most relevant information for hospital referral purposes based on a literature review and qualitative research. Primary survey data were collected (May–June 2021) on a sample of 591 referring orthopedists in Germany and analyzed using structural equation modeling. Participating orthopedists were recruited using a sequential mixed-mode strategy and randomly allocated to work with HRCs in the presence (intervention) or absence (control) of PROs. Results: Overall, 420 orthopedists (mean age 53.48, SD 8.04) were included in the analysis. The presence of PROs on HRCs was not associated with an increased intention to use HRCs (p = 0.316). Performance expectancy was shown to be the most important determinant for using HRCs (path coefficient: 0.387, p <.001). However, referring physicians have doubts as to whether HRCs can help them. We identified “complication rate” and “the number of cases treated” as most important for the hospital referral decision making; PROs were rated slightly less important. Conclusions: This study underpins the purpose of HRCs, namely to support referring physicians in searching for a hospital. Nevertheless, only a minority would support the use of HRCs for the next hospital search in its current form. We showed that presenting relevant information on HRCs did not increase their use intention.
CRIS-Team Scopus Importer:2023-04-28
Keywords: Hospital referrals; Hospital report cards; Patient-reported outcomes; Public reporting; UTAUT

The elicitation of patient and physician preferences for calculating consumer-based composite measures on hospital report cards: results of two discrete choice experiments - Emmert, Martin; Rohrbacher, Stefan; Meier, Florian; Heppe, Laura; Drach, Cordula; Schindler, Anja; Sander, Uwe; Patzelt, Christiane; Frömke, Cornelia; Schöffski, Oliver; Lauerer, Michael (European Journal of Health Economics, 2023)
Purpose: The calculation of aggregated composite measures is a widely used strategy to reduce the amount of data on hospital report cards. Therefore, this study aims to elicit and compare preferences of both patients as well as referring physicians regarding publicly available hospital quality information Methods: Based on systematic literature reviews as well as qualitative analysis, two discrete choice experiments (DCEs) were applied to elicit patients’ and referring physicians’ preferences. The DCEs were conducted using a fractional factorial design. Statistical data analysis was performed using multinomial logit models Results: Apart from five identical attributes, one specific attribute was identified for each study group, respectively. Overall, 322 patients (mean age 68.99) and 187 referring physicians (mean age 53.60) were included. Our models displayed significant coefficients for all attributes (p < 0.001 each). Among patients, “Postoperative complication rate” (20.6%; level range of 1.164) was rated highest, followed by “Mobility at hospital discharge” (19.9%; level range of 1.127), and ‘‘The number of cases treated” (18.5%; level range of 1.045). In contrast, referring physicians valued most the ‘‘One-year revision surgery rate’’ (30.4%; level range of 1.989), followed by “The number of cases treated” (21.0%; level range of 1.372), and “Postoperative complication rate” (17.2%; level range of 1.123) Conclusion: We determined considerable differences between both study groups when calculating the relative value of publicly available hospital quality information. This may have an impact when calculating aggregated composite measures based on consumer-based weighting.
CRIS-Team Scopus Importer:2023-12-22
Keywords: Composite measures; Discrete choice experiment; Hospital choice; Hospital report cards; Public reporting

The use intention of hospital report cards among patients in the presence or absence of patient-reported outcomes - Emmert, Martin; Schindler, Anja; Drach, Cordula; Sander, Uwe; Patzelt, Christiane; Stahmeyer, Jona; Kühnel, Elias; Lauerer, Michael; Nagel, Eckhard; Frömke, Cornelia; Schöffski, Oliver; Heppe, Laura (Health policy (Amsterdam, Netherlands), 2022)
Background: So far, the adoption of hospital report cards (HRCs) falls short of expectations. One promising strategy is to modify the content of HRCs by presenting patient-reported outcomes (PROs). Objective: To identify the key determinants influencing patients to use HRCs for hospital decision making and determine the effect of presenting PROs on HRCs on their use intention. Methods: Primary survey data were collected (5/6–2021) on a sample of 2000 randomly selected insurees from a German statutory health insurance who have undergone elective hip arthroplasty surgery. Results: Overall, 447 participants (mean age 66.56) completed the survey and were included in the analysis. Respondents rated “PROs” as most important for the hospital choice followed by “Mobility at hospital discharge” and “Confirmed diagnosis rate”. Patients generally perceive HRCs to be a good idea that makes searching for a hospital more interesting. We identified attitude and social influence as the most important determinants for using HRCs (p<.001 each). The presence of PROs on HRCs was not associated with an increased intention to use HRCs neither in our descriptive analysis (p=.593), nor in our research model (p=.763). Conclusions: Patients value PROs to be an important information for choosing a hospital. Nevertheless, health policy makers should note that presenting PROs on HRCs as a single approach is not likely to increase the use of HRCs.
CRIS-Team Scopus Importer:2022-04-15